A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Petrophysically Constrained ERT for Resolving Spatiotemporal Clogging Evolution in Sand Filtration Systems - Ho Wen Chen; Winn-Jung Huang; Chih Cheng Chang; Chien-Yuan Chen; Hsin-Chang Liu; Yu-Ju Chang (Environmental Processes, 2026)

Late Holocene human-environment interactions on a small island of the Taiwan Strait - Ranjan Kumar Mohanty; Abdur Rahman; Yi-Chen Ho; Yu-Chen Lu; Cheng-Tao Lin; Hung-Chun Chao; Ling-Ho Chung; Chin-Yung Chao; Liang-Chi Wang (Quaternary International, 2026)

Experimental investigation of ullage and wall-orifice effects on heptane pool fire burning behavior and burn enhancement - Chia-Yu Huang; Yi-Chen Tsai; Sz-Cheng Kao; Hsin-Hsiu Ho (Process Safety and Environmental Protection, 2026)

Multiple benefits of biochar for remediating contaminated mining soils: heavy metal stabilization, carbon sequestration, and ecological function restoration - Yibo Cheng; Weiying Feng; Yu Wang; Fang Yang; Qingfeng Miao; Chiamin Ho; Yaoqiang Huo; Haiqing Liao (Chemical Engineering Journal, 2026)

Ferroptosis modulation by Toxoplasma gondii suppresses sodium iodate–driven age-related macular degeneration - Xin-Cheng Wang; Guan-Hao Hong; Yu-Sun Yun; In-Wook Choi; Jaemin Yuk; Guang-Ho Cha (Genes & Genomics, 2026)

Pharmacological effects of cardamonin in metabolic diseases: a review on preclinical studies - Aizhi Zhang; AbdulRahman Muthanna; Yu Zhao Lee; Xuan Xin Yew; Rieyshmondraj Selvanathan; Zuo Shan Reuel Gan; Ji Wei Tan; Yu-Cheng Ho; Ming Tatt Lee; Chau Ling Tham (Inflammopharmacology, 2026)

A novel approach for utilizing UAV imaging and deep learning techniques for river channel measurement and flood simulation - Jen-Yu Han; Chun-Jia Huang; Yuan-Shun Chang; Yen-Cheng Lin; Hao-Che Ho (Geomorphology, 2026)

Impacts of period-specific particulate matter exposure on COPD phenotypes: Rapid lung function decline - Po-Hao Feng; I-Jung Liu; Rachel Chien; Kang-Yun Lee; Kuan-Yuan Chen; Wen-Te Liu; Ying-Ying Chen; Yen-Ling Chen; Kun-Ta Lee; Shu-Chuan Ho; Arnab Majumdar; Jiunn-Horng Kang; et al. (Atmospheric Environment, 2026)

Investigating temporal PM2.5 exposure in relation to rapid lung-function decline among COPD patients: A retrospective study - Kang-Yun Lee; Rachel Chien; Kuan-Yuan Chen; Ying-Ying Chen; Wen-Te Liu; Po-Hao Feng; Kun-Ta Lee; Shu-Chuan Ho; Arnab Majumdar; Jiunn-Horng Kang; Wun-Hao Cheng; I-Jung Liu; et al. (Atmospheric Pollution Research, 2026)

A 24-year record of Cetacean strandings in Taiwanese waters: Signals of escalating threats - Yun Ho; Lien-Siang Chou; Chiou-Ju Yao; Wei-Lien Chi; Hao-Ven Wang; Ing Chen; Hsin-Yi Yu; Pei-Ying Wu; Wei-Cheng Yang (Marine Environmental Research, 2026)

Neurobiology of chronic caffeine use and withdrawal: Mechanisms, effects and implications - Yu Zhao Lee; Ker Ni Chua; Fui-Ling Voon; Chau Ling Tham; Yu-Cheng Ho; Ming Tatt Lee (Food and Chemical Toxicology, 2026)

Room-Temperature Fabrication of Dual-Functional SiO2/TiO2 Coating for Photovoltaic Efficiency Enhancement: From Laboratory Development to Field Validation - Pengge Wang; Xinwei Li; Ning Zhang; Yue Zhai; Zhenyu Wang; Long Cui; Suixin Liu; Wingkei Ho; Yu Huang; Shun-cheng Lee (Aerosol Science and Engineering, 2025)

Impact of vancomycin and Clostridioides difficile on the secretome and pathogenicity of Clostridium innocuum - Yi-Ywan M. Chen; Kun-Yi Chien; Hui-Ru Shieh; Cai-Jie Luo; Yu-Xun Chang; Chuan Chiang-Ni; Chih-Ho Lai; Cheng-Hsun Chiu (Medical Microbiology and Immunology, 2025)

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

Distinct effects of methylglyoxal-derived hydroimidazolone 1, N-carboxyethyllysine, and an advanced glycation end product-rich diet on lipid metabolism, gut microbiota, and secondary bile acids in high-fat diet-induced obese mice - Shih-Fang Huang; Yu-Ting Chang; Shih-Min Hsia; Kai-Wei Liao; Cheng-Yi Tsai; Shih-Yi Huang; Chi-Tang Ho; Wei-Lun Hung (Food Chemistry, 2025)

Antidiabetic potentials of gypenosides: A review on the preclinical effects in glucose and insulin modulation as well as diabetes-related complications - Yu Zhao Lee; Audrey Siew Foong Kow; Qi Long Lee; Luis Wei Cheng Lim; Rohana Yusof; Chau Ling Tham; Yu-Cheng Ho; Ming Tatt Lee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Microplastic exposure aggravates pneumococcus-induced inflammation in macrophages by activating ferroptosis - Ko-Wei Chang; Jo-Tsen Chen; Chun-Ning Chuang; Dang Thi Thanh Thao; Yu-Tsen Huang; Hui-Yu Wu; Ming-Ling Kuo; Kuo-Chin Kao; Cheng-Hsun Chiu; Chih-Ho Lai (Journal of Hazardous Materials, 2025)

Alisertib inhibits acute myeloid leukemia cell growth by inhibiting STAT3 activation - Pang-Ting Cheng; Ho Lin; Yu-Chiao Cheng; Tzu-Hung Hsiao; Pei-Pei Jhan; Jia-Rung Tsai; Mei-Chih Chen; Tai-Lin Chen; Chieh-Lin Jerry Teng (Toxicology and Applied Pharmacology, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Unveiling the source contributions of fine and coarse particulate matter using PM-bound metals and PMF-AI modeling - Chin-Yu Hsu; Akshansha Chauhan; Yi-Wen Chen; Meng-Ying Jian; Kuan-Ting Liu; Thi Phuong Thao Ho; Yu-Hsiang Cheng (Atmospheric Pollution Research, 2025)

Analysis of Wind–Wave Relationship in Taiwan Waters - Kai-Ho Cheng; Chih-Hsun Chang; Yi-Chung Yang; Yu-Hao Tseng; Chung-Ru Ho; Tai-Wen Hsu; Dong-Jiing Doong (Journal of Marine Science and Engineering, 2025)
The relationship between wind and waves has been extensively studied over time. However, understanding the local wind and wave relationship remains crucial for advancing renewable energy development and optimizing ocean management strategies. This study used wind and wave data collected by the ten weather buoys in the waters surrounding Taiwan to analyze regional sea states. The relationship between wind speed and significant wave height (SWH) was examined using regression analysis. Additionally, machine learning techniques were employed to assess the relative importance of features contributing to SWH growth. The regression analysis revealed that SWH in the waters surrounding Taiwan was not fully developed, with notable discrepancies observed between the waters east and west of Taiwan. According to the power law formula describing the relationship between wind speed and SWH, the eastern waters exhibited a larger prefactor coupled with a smaller scaling exponent, while the western waters manifested a converse parametric configuration. Through an evaluation of four machine learning algorithms, it was determined that wind speed is the most influential factor driving these regional differences, especially in the waters west of Taiwan. Beyond wind speed, air pressure or temperature emerged as the secondary feature factor governing wind–wave interactions in the waters east of Taiwan.

Thermoelectric performance in Ag2Se nanocomposites: The role of interstitial Ag and Pb orbital hybridization - Khak Ho Lim; Yuxuan Xia; Lixiang Xu; Mingjun Zhao; Mingquan Li; Ye Cheng; Jiale Mao; Shuang Wang; Lei Chen; Sai Wing Tsang; Pingwei Liu; Qingyue Wang; et al. (Chemical Engineering Journal, 2025)

Systematics and evolutionary history of raft and nursery‐web spiders (Araneae: Dolomedidae and Pisauridae) - Kuang‐Ping Yu; Ren‐Chung Cheng; Charles R. Haddad; Akio Tanikawa; Brogan L. Pett; Luis N. Piacentini; Ho Yin Yip; Yuya Suzuki; Arnaud Henrard; Christina J. Painting; Cor J. Vink; Eileen A. Hebets; et al. (Zoologica Scripta, 2025)
Pisauridae are a global and heterogeneous assemblage of spider genera with diverse morphologies and lifestyles. So far, the monophyly of Pisauridae and the inclusion of fishing spiders ( Dolomedes ) in this family have not been thoroughly tested. Here, we amend the systematics and classification of these lineages within a UCE phylogenomic framework and through a detailed morphological reappraisal. For estimations of their evolutionary age, we perform and compare outcomes from two divergence estimation approaches, an a posteriori likelihood, and an a priori Bayesian. Phylogenies reject the monophyly of both Pisauridae and Dolomedes : (1) Focal Clade I groups true Pisauridae genera including Pisaura ; (2) Focal Clade II contains Blandinia and is sister to Trechaleidae and Lycosidae; (3) Focal Clade III groups Dolomedes , Megadolomedes , and Ornodolomedes , and is sister to Blandinia , Trechaleidae, and Lycosidae. We therefore propose to delimit Pisauridae by removing Dolomedidae rank resurrected (including Dolomedes , Bradystichus , Megadolomedes , Caledomedes , Mangromedes , Ornodolomedes , and Tasmomedes ) and Blandinia incertae sedis . Likelihood and Bayesian time calibration approaches yield comparable divergence estimations: Pisauridae origin is estimated at 29–40 Ma; Blandinia 21–34 Ma; Dolomedidae 10–17 Ma; Dolomedes 9–16 Ma. Reconstructions suggest that the evolution of terrestrial and web‐building lifestyles from semi‐aquatic ancestors in Pisauridae coincided with cooling and drying climates during the mid‐Miocene, but this was not the case in the few recent cases of terrestrialization in Dolomedes species. This historic reconstruction illustrates how climatic changes, or rapid radiation, can drive lifestyle diversification.

Harvesting rice straw management synergies for lifecycle environmental and economic sustainability - Suraj Negi; Yu-Chi Cheng; Shan-Li Wang; Shuay-Tsyr Ho; Shu-Yuan Pan (Science of The Total Environment, 2025)

Unveiling secondary inorganic PM2.5 pollution in northern Taiwan: The role of aerosol acidity and transformation processes - Ankita Katoch; Chi-Chi Lin; Yu-Chieh Ting; Thi Phuong Thao Ho; Kuan-Ting Liu; Atar Singh Pipal; Yu-Hsiang Cheng (Science of The Total Environment, 2025)

Methane Index and TEX86 values in cold seep sediments: Implications for paleo-environmental reconstructions - Sze Ling Ho; Yu-Shih Lin; Pei-Ling Wang; Tzu-Ting Chen; Pei-Ting Lee; Hui-Hsin Wang; Tzu-Jung Cheng; Yun-Ju Wang; Chih-Chieh Su; Min-Te Chen (Geochimica et Cosmochimica Acta, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Year-round natural spawning, early ontogeny, and larval rearing of the painted sweetlips, Diagramma pictum (Thunberg, 1792) in a hatchery: Potential as a new species for mariculture - Pei-Sheng Chiu; Bo-Hong Yu; Yu-Hsin Tu; Yeong-Torng Chu; Cheng-Hsuan Huang; Shine-Wei Ho; Sun-Hon Lin; Shinn-Lih Yeh; Ming-Yih Leu (Aquaculture, 2025)

Application of Computational Fluid Dynamics and Semi-Empirical Speed Loss Prediction for Weather Routing - Chih-Wen Cheng; Yu-An Tzeng; Ming-Hsiung Chang; Shang-Chi Liu; Ho-King Cheung; Ching-Yeh Hsin (Journal of Marine Science and Engineering, 2024)
This study presents an optimized system for ship route planning. Computational fluid dynamics simulations were used to modify Kwon’s semi-empirical speed loss estimation method, enabling efficient route planning under variable sea conditions. The study focused on improving the prediction of speed loss in irregular waves for container ships and further applying this to ship-optimized voyage planning. Dynamic programming was used for optimized voyage planning by modifying the ship course in response to meteorological data; this approach could balance both energy efficiency and safety. The modified speed loss predictions aligned closely with the simulation results, enhancing the reliability of weather routing decisions. Case studies for trans-Pacific and trans-Atlantic voyages demonstrated that the proposed system could significantly reduce the voyage time. These findings highlight the potential of real-time updates in voyage planning. The proposed system is a valuable tool for captains and fleet managers. The applicability of this system can be further broadened by validating it on different ship types.

Exploring the characteristics and source-attributed health risks associated with polycyclic aromatic hydrocarbons and metal elements in atmospheric PM2.5 during warm and cold periods in the northern metropolitan area of Taiwan - Yi-Wen Chen; Thi Phuong Thao Ho; Kuan-Ting Liu; Meng-Ying Jian; Ankita Katoch; Yu-Hsiang Cheng (Environmental Pollution, 2024)

Ischemic cardiac stromal fibroblast-derived protein mediators in the infarcted myocardium and transcriptomic profiling at single cell resolution - Ed Cha; Sung Ho Hong; Taj Rai; Vy La; Pranav Madabhushi; Darren Teramoto; Cameron Fung; Pauline Cheng; Yu Chen; Angelo Keklikian; Jeffrey Liu; William Fang; et al. (Functional & Integrative Genomics, 2024)
This article focuses on screening the major secreted proteins by the ischemia-challenged cardiac stromal fibroblasts (CF), the assessment of their expression status and functional role in the post-ischemic left ventricle (LV) and in the ischemia-challenged CF culture and to phenotype CF at single cell resolution based on the positivity of the identified mediators. The expression level of CRSP2, HSP27, IL-8, Cofilin-1, and HSP90 in the LV tissues following coronary artery bypass graft (CABG) and myocardial infarction (MI) and CF cells followed the screening profile derived from the MS/MS findings. The histology data unveiled ECM disorganization, inflammation and fibrosis reflecting the ischemic pathology. CRSP2, HSP27, and HSP90 were significantly upregulated in the LV-CABG tissues with a concomitant reduction ion LV-MI whereas Cofilin-1, IL8, Nrf2, and Troponin I were downregulated in LV-CABG and increased in LV-MI. Similar trends were exhibited by ischemic CF. Single cell transcriptomics revealed multiple sub-phenotypes of CF based on their respective upregulation of CRSP2, HSP27, IL-8, Cofilin-1, HSP90, Troponin I and Nrf2 unveiling pathological and pro-healing phenotypes. Further investigations regarding the underlying signaling mechanisms and validation of sub-populations would offer novel translational avenues for the management of cardiac diseases.

Insight into the diurnal variations and potential sources of ambient PM2.5-bound polycyclic aromatic hydrocarbons during spring in Northern Taiwan - Yi-Wen Chen; Kuan-Ting Liu; Ho Thi Phuong Thao; Meng-Ying Jian; Yu-Hsiang Cheng (Journal of Hazardous Materials, 2024)

Design and assessment of highly stable norfloxacin/ Ca-montmorillonite (STx-1b) as oral beads - Po-Hsiang Chang; Chenxing Liang; Yating Yang; Yaqi Wen; Cheng-I Lee; Juin-Yen Ho; Chien-Yen Chen; Yu-Min Tzou (Applied Clay Science, 2024)

Applying the total carbon–black carbon approach method to investigate the characteristics of primary and secondary carbonaceous aerosols in ambient PM2.5 in northern Taiwan - Ankita Katoch; Muneer Abbass; Yi-Wen Chen; Thi Phuong Thao Ho; Chun-Fu Fan; Yu-Hsiang Cheng (Science of The Total Environment, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Optical properties and radiative forcing of carbonaceous aerosols in a valley city under persistent high temperature - Chunyan Li; Bianhong Zhou; Junhui Zhang; Lihua Jiao; Kaijing Cheng; Long Chen; Yu Li; Yongqiang Li; Steven Sai Hang Ho; Zhongtao Wen (Science of The Total Environment, 2024)

Dinaciclib inhibits the growth of acute myeloid leukemia cells through either cell cycle-related or ERK1/STAT3/MYC pathways - Chieh-Lin Jerry Teng; Pang-Ting Cheng; Yu-Chiao Cheng; Jia-Rung Tsai; Mei-Chih Chen; Ho Lin (Toxicology in Vitro, 2024)

Impact of occupational noise exposure on the hearing level in hospital staffs: a longitudinal study - Tang-Chuan Wang; You-Cheng Yu; Alan Hsu; Jia-Yi Lin; Yung-An Tsou; Chiu-Shong Liu; Kai-Jen Chuang; Wen-Chi Pan; Chin-An Yang; Sung-Lin Hu; Chien-Yi Ho; Tzu-Liang Chen; et al. (Environmental Science and Pollution Research, 2024)

Thromboembolic events following a pit viper bite from Protobothrops mucrosquamatus (Taiwan Habu): A report of two cases - I. Sun; Siou-Ting Lee; Yu-Guang Chen; Yan-Chiao Mao; Feng-Chen Chen; Yen-Hsiu Chen; Shih-Hung Tsai; Cheng-Hsuan Ho (Toxicon, 2024)

Critical Roles of Surface-Enhanced Heterogeneous Oxidation of SO2 in Haze Chemistry: Review of Extended Pathways for Complex Air Pollution - Zihao Zhang; Haiwei Li; Wingkei Ho; Long Cui; Qihui Men; Li Cao; Yunjiang Zhang; Junfeng Wang; Cheng Huang; Shun-cheng Lee; Yu Huang; Mindong Chen; et al. (Current Pollution Reports, 2024)

A longitudinal study on the change in sleep across three waves of the COVID-19 outbreaks in Hong Kong - Denise Shuk Ting Cheung; Branda Yee-Man Yu; Simon Ching Lam; Doris Yin Ping Leung; Ka-Fai Chung; Fiona Yan-Yee Ho; Shu-Cheng Chen; Wing-Fai Yeung (Sleep and Biological Rhythms, 2024)

Field observations of C2 and C3 organosulfates and insights into their formation mechanisms at a suburban site in Hong Kong - Yuchen Wang; Shumin Liang; Michael Le Breton; Qiong Qiong Wang; Qianyun Liu; Chin Hung Ho; Bin Yu Kuang; Cheng Wu; Mattias Hallquist; Rongbiao Tong; Jian Zhen Yu (Science of The Total Environment, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Impaired Ventrolateral Periaqueductal Gray-Ventral Tegmental area Pathway Contributes to Chronic Pain-Induced Depression-Like Behavior in Mice - Ming Tatt Lee; Wei-Hao Peng; Cheng-Chun Wu; Hung-Wei Kan; Deng-Wu Wang; Yu-Ning Teng; Yu-Cheng Ho (Molecular Neurobiology, 2023)

Dynamic total factors’ environmental efficiency in European union countries - Ching-Cheng Lu; Yung-ho Chiu; I-Fang Lin; Tai-Yu Lin (Environment, Development and Sustainability, 2023)

Captive Reproductive Behavior, Spawning, and Early Development of White-Barred Goby Amblygobius phalaena (Valenciennes, 1837) and Examined Larval Survival and Viability at Different Water Temperatures and Salinities - Pei-Sheng Chiu; Shine-Wei Ho; Cheng-Hsuan Huang; Yen-Chun Lee; Yu-Hung Lin (Fishes, 2023)
White-barred goby Amblygobius phalaena is a highly valued marine ornamental fish, but its captive reproduction and early life history are poorly understood. In this study, the captive reproductive behavior, early development, and optimal temperature and salinity for the larval survival and viability of A. phalaena were investigated for the first time. Spawning occurred between 11:00 and 13:00, with the breeding pairs naturally spawning 24 times from 1 June 2021 to 30 June 2022. The fecundity ranged from 11,022 to 95,858 eggs per spawning event. Hatching occurred approximately 81 h and 26 min after fertilization at a temperature of 27.0 ± 0.9 °C. Newly hatched larvae had a total length (TL) of 1.91–2.03 mm with 24–26 somites. The larvae transformed into juveniles at 30 days post-hatch. Experiments were conducted at different temperatures (21, 24, 27, 30, and 33 °C) and salinities (18, 24, 30, and 36 ppt) to determine the optimal conditions for larval survival and viability. The results indicate that the most suitable conditions in terms of temperature were in the range of 21–27 °C and 30 ppt for salinity. These findings provide valuable insights for the future development of captive-breeding techniques and the commercial production of other marine ornamental gobies.

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Source-oriented risk and lung-deposited surface area (LDSA) of ultrafine particles in a Southeast Asia urban area - Tse-Lun Chen; Chen-Hao Lai; Yu-Cheng Chen; Yu-Hsuan Ho; Albert Y. Chen; Ta-Chih Hsiao (Science of The Total Environment, 2023)

Flow measurement in open channels using imaging techniques in conjunction with a convolutional neural network - Hao-Che Ho; Yu-Wei Chiu; Ting-Yu Chen; Yen-Cheng Lin (Journal of Hydrology, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Bioremediation potential of cadmium by recombinant Escherichia coli surface expressing metallothionein MTT5 from Tetrahymena thermophila - Che-Wei Lu; Hsin-Cheng Ho; Chao-Ling Yao; Tsung-Yu Tseng; Chih-Ming Kao; Ssu-Ching Chen (Chemosphere, 2023)

Association between cold weather, influenza infection, and asthma exacerbation in adults in Hong Kong - Xi Xiong; Yuchen Wei; Holly Ching Yu Lam; Carlos King Ho Wong; Steven Yuk Fai Lau; Shi Zhao; Jinjun Ran; Conglu Li; Xiaoting Jiang; Qianying Yue; Wei Cheng; Huwen Wang; et al. (Science of The Total Environment, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Two-stage dynamic data envelopment analysis measuring the overall efficiency and productivity changes of industry and agriculture in EU countries - Ching-Cheng Lu; I-Fang Lin; Tai-Yu Lin; Yung-ho Chiu (Journal of Cleaner Production, 2023)

Intelligent films of marine polysaccharides and purple cauliflower extract for food packaging and spoilage monitoring - Han-Lun Huang; I-Lin Tsai; Chi Lin; Yu-Hao Hang; Yi-Cheng Ho; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Equilibrative Nucleoside Transporter 1 is a Target to Modulate Neuroinflammation and Improve Functional Recovery in Mice with Spinal Cord Injury - Kuan-Yu Chen; Chiao-Shin Lu; Cheng-Yoong Pang; Chin-Jui Ho; Kuo-Chen Wu; Hsiu-Wei Yang; Hsin-Lin Lai; Yijuang Chern; Chun-Jung Lin (Molecular Neurobiology, 2023)

Rapid antidepressant-like effects of muscarinic receptor antagonists require BDNF-dependent signaling in the ventrolateral periaqueductal gray - Hung-Wei Kan; Wei-Hao Peng; Cheng-Chun Wu; Deng-Wu Wang; Ming Tatt Lee; Yung-Kuo Lee; Tian-Huei Chu; Yu-Cheng Ho (Psychopharmacology, 2022)

Use of an Effective Variance Chemical Mass Balance Model for Source Apportionment of Metal Elements in a Polluted River - Pei-Yuan Hsieh; Chi-Chang Ho; Gen-Shuh Wang; Yuan-Cheng Hsu; Di-Wen Wang; Yu-Man Shang; Chang-Fu Wu (Environmental Processes, 2022)

Assessment of brain connectome alterations in male chronic smokers using structural and generalized q-sampling MRI - Jun-Cheng Weng; Yu-Chen Chuang; Li-Bang Zheng; Ming-Shih Lee; Ming-Chou Ho (Brain Imaging and Behavior, 2022)

Air pollution associated with cognitive decline by the mediating effects of sleep cycle disruption and changes in brain structure in adults - Chen-Chen Lo; Wen-Te Liu; Yueh-Hsun Lu; Dean Wu; Chih-Da Wu; Ting-Chieh Chen; Yu-Ting Fang; Yu-Chun Lo; You-Yin Chen; Lo Kang; Cheng-Yu Tsai; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Controls of Submarine Canyons Connected to Shore during the LGM Sea-Level Rise: Examples from Taiwan - Cheng-Shing Chiang; Ho-Shing Yu (Journal of Marine Science and Engineering, 2022)
During the Last Glacial Maximum (LGM) (~20,000 years ago), the sea level was lower than that during the present day by 120 m and the heads of most submarine canyons were close or connected to the coastline or shore, with enhanced terrestrial sediment input due to direct connections with river mouths. This was followed by a relative sea-level rise of 120 m and the migration of coastlines landward. As a result, the heads of some paleo-submarine canyons were no longer near river mouths or connected to the shore. Such canyons became inactive due to the lack of terrestrial sediment input. Only 4% of the world’s submarine canyons reach the coastline and remain active today. Among 13 submarine canyons off the shore of Taiwan, we identified seven (n = 7, 54%) that remain connected to the shore and are active during the present-day highstand. The purpose of this study is to determine the key controls of canyon heads that remain connected to the shore with terrestrial sediment input during the Holocene sea-level rise. As a result of high uplift rates, narrow coastal range, steep gradients, frequent earthquakes, and typhoon development in the Taiwan mountain belt, Taiwan has the highest-yield river and sediment supply. This has led to the transportation of large volumes of sediment to the surrounding deep seas. Narrow steep shelves and large sediment volumes associated with small mountain rivers are the main controls involved in the development of shore-connected canyons on the active Taiwan margin. Shore-connected canyons are present in greater numbers in the major earthquake zone on the eastern Taiwan margin. Frequent earthquake events are another significant factor in the occurrence of shore-connected canyons in the Taiwan region.

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Organic carbon and acidic ions in PM2.5 contributed to particle bioreactivity in Chinese megacities during haze episodes - Kin-Fai Ho; Ya-Chun Lee; Xinyi Niu; Hongmei Xu; Renjian Zhang; Jun-Ji Cao; Cheng-Yu Tsai; Ta-Chih Hsiao; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

Associations between lung-deposited dose of particulate matter and culture-positive pulmonary tuberculosis pleurisy - Kuan-Jen Bai; Nguyen Thanh Tung; Ta-Chih Hsiao; Tsai-Ling Chen; Kian Fan Chung; Shu-Chuan Ho; Cheng-Yu Tsai; Jen-Kun Chen; Chun-Nin Lee; Kang-Yun Lee; Chih-Cheng Chang; Tzu-Tao Chen; et al. (Environmental Science and Pollution Research, 2022)

Household environmental microbiota influences early‐life eczema development - Le Duc Huy Ta; Carina Jing Xuan Tay; Christophe Lay; Paola Florez de Sessions; Cheryl Pei Ting Tan; Michelle Jia Yu Tay; Hui Xing Lau; Atiqa Binte Zulkifli; Gaik Chin Yap; Elizabeth Huiwen Tham; Eliza Xin Pei Ho; Anne Eng Neo Goh; et al. (Environmental Microbiology, 2021)
Summary Exposure to a diverse microbial environment during pregnancy and early postnatal period is important in determining predisposition towards allergy. However, the effect of environmental microbiota exposure during preconception, pregnancy and postnatal life on development of allergy in the child has not been investigated so far. In the S‐PRESTO (Singapore PREconception Study of long Term maternal and child Outcomes) cohort, we collected house dust during all three critical window periods and analysed microbial composition using 16S rRNA gene sequencing. At 6 and 18 months, the child was assessed for eczema by clinicians. In the eczema group, household environmental microbiota was characterized by presence of human‐associated bacteria Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium at all time points, suggesting their possible contributions to regulating host immunity and increasing the susceptibility to eczema. In the home environment of the control group, putative protective effect of an environmental microbe Planomicrobium ( Planococcaceae family) was observed to be significantly higher than that in the eczema group. Network correlation analysis demonstrated inverse relationships between beneficial Planomicrobium and human‐associated bacteria ( Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium ). Exposure to natural environmental microbiota may be beneficial to modulate shed human‐associated microbiota in an indoor environment.

Morphological Significance and Relation of Ecosystems of Submarine Canyons off SW Taiwan - Cheng-Shing Chiang; Ho-Shing Yu (Journal of Marine Science and Engineering, 2021)
There are four shelf-incising submarine canyons off SW Taiwan. They are distributed along the active continental margin, which is periodically flushed by gravity flows. Shelf-incising canyons, such as Kaoping Canyon, may not only be affected by oceanographic conditions but also by extreme climate change due to the direct input of river sediment. In the canyons along the SW margin of Taiwan, strong sedimentary flows are reflected in highly abundant nutrient input and physical disturbances. The Kaoping Canyon possesses habitats that promote biodiversity but that are sensitive to environmental change. The aims of this study are to review the canyons along the SW margin of Taiwan and to present their geomorphological features and associated ecosystems.

Evaluating the energy, health efficiency, and productivity in OECD - Ching-Cheng Lu; Yung-ho Chiu; Chih-Yu Yang; Tai-Yu Lin (Environmental Geochemistry and Health, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Assessment of climate change effects on alpine summit vegetation in the transition of tropical to subtropical humid climate - Chu-Chia Kuo; Yu Su; Ho-Yih Liu; Cheng-Tao Lin (Plant Ecology, 2021)

Association between functional brain alterations and neuropsychological scales in male chronic smokers using resting-state fMRI - Jun-Cheng Weng; Shih-Yu Huang; Ming-Shih Lee; Ming-Chou Ho (Psychopharmacology, 2021)

Efficacy of a Smartphone Hearing Aid Simulator - Cheng-Yu Ho; Pei-Chun Li; Shuenn-Tsong Young; Ying-Hui Lai (Journal of Medical and Biological Engineering, 2020)

Sources and monthly and seasonal concentration variation study of atmospheric particulates and particles-bound PAEs - Guor-Cheng Fang; Tse-Tsung Ho; Yu-Cheng Chen; Yuan-Jie Zhuang; Chao-Lang Kao; Gui-Ren Liang (Environmental Geochemistry and Health, 2020)

Three types of modern submarine canyons on the tectonically active continental margin offshore southwestern Taiwan - Cheng-Shing Chiang; Kan-Hsi Hsiung; Ho-Shing Yu; Song-Chuen Chen (Marine Geophysical Research, 2020)

Polymethoxyflavones: Chemistry and Molecular Mechanisms for Cancer Prevention and Treatment - Yen-Chen Tung; Ya-Chun Chou; Wei-Lun Hung; An-Chin Cheng; Roch-Chui Yu; Chi-Tang Ho; Min-Hsiung Pan (Current Pharmacology Reports, 2019)

Herpes zoster increased risk of neuralgic amyotrophy: a retrospective, population-based matched cohort study - Tsung-Yen Ho; Chi-Hsiang Chung; Yu-Ping Shen; Liang-Cheng Chen; Wu-Chien Chien; Yung-Tsan Wu (Journal of NeuroVirology, 2019)

Leucocin C-607, a Novel Bacteriocin from the Multiple-Bacteriocin-Producing Leuconostoc pseudomesenteroides 607 Isolated from Persimmon - Yi-sheng Chen; Hui-chung Wu; Cheng-yu Kuo; Yu-wei Chen; Sin Ho; Fujitoshi Yanagida (Probiotics and Antimicrobial Proteins, 2018)

Peri-Therapeutic Quantitative Flow Analysis of Endovascular Revascularization for Ischemic Stroke Patients on Digital Subtraction Angiography - Shih-Neng Yang; Yu-Yi Lin; Tsung-Jung Ho; Shi-Yann Cheng; Yu-Rou Chiou; Chun-Han Liao; Geoffrey G. Zhang; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Mapping brain functional alterations in betel-quid chewers using resting-state fMRI and network analysis - Jun-Cheng Weng; Yu-Syuan Chou; Guo-Joe Huang; Yeu-Sheng Tyan; Ming-Chou Ho (Psychopharmacology, 2018)

Using major nutrient concentrations to derive vertical movement of water masses in the coastal region of eastern Taiwan - Su-Cheng Pai; Sen Jan; Tung-Yuan Ho; Jin-Yuan Liu; Ken-Sheng Chu; Wen-Huei Lee; Cheng-Yun Wang; Ping-Yi Huang; Hung-Yu Hsu; Yiing-Jang Yang (Journal of Oceanography, 2017)

Far infrared promotes wound healing through activation of Notch1 signaling - Yung-Ho Hsu; Yuan-Feng Lin; Cheng-Hsien Chen; Yu-Jhe Chiu; Hui-Wen Chiu (Journal of Molecular Medicine, 2017)

Statistical features of eddies approaching the Kuroshio east of Taiwan Island and Luzon Island - Yu-Hsin Cheng; Chung-Ru Ho; Quanan Zheng; Bo Qiu; Jianyu Hu; Nan-Jung Kuo (Journal of Oceanography, 2017)

Three-Dimensional Bi $$_{5}$$ 5 O $$_{7}$$ 7 I Photocatalysts for Efficient Removal of NO in Air Under Visible Light - Wei Wang; Yu Huang; Xiaochao Zhang; Jun-ji Cao; Wingkei Ho; Shun Cheng Lee (Aerosol Science and Engineering, 2017)

Preliminary Measurements of Binaural Masking-Level Difference When Using Hearing Aids for Sensorineural Hearing Loss - Cheng-Yu Ho; Pei-Chun Li; Shuenn-Tsong Young; Wen-Ying Yeh; Chih-Hung Wang; Woei-Chyn Chu (Journal of Medical and Biological Engineering, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Seismic characteristics, morphology and formation of the ponded Fangliao Fan off southwestern Taiwan, northern South China Sea - Kan-Hsi Hsiung; Ho-Shing Yu; Cheng-Shing Chiang (Geo-Marine Letters, 2014)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

Sesamin extends the mean lifespan of fruit flies - Yuanyuan Zuo; Cheng Peng; Yintong Liang; Ka Ying Ma; Ho Yin Edwin Chan; Yu Huang; Zhen-Yu Chen (Biogerontology, 2013)

Mutations in the NRG1 gene are associated with Hirschsprung disease - Clara Sze-Man Tang; Elly Sau-Wai Ngan; Wai-Kiu Tang; Man-Ting So; Guo Cheng; Xiao-Ping Miao; Thomas Yuk-Yu Leon; Brian Man-Chun Leung; Kenneth-Jeremy W. S. Hui; Vincent Hang-Chai Lui; Yan Chen; Ivy Hau-Yee Chan; et al. (Human Genetics, 2012)

Increasing trend of primary NO2 exhaust emission fraction in Hong Kong - Linwei Tian; Sarah R. Hossain; Hualiang Lin; Kin Fai Ho; Shun Cheng Lee; Ignatius T. S. Yu (Environmental Geochemistry and Health, 2011)

Four new xarifiid copepods (Poecilostomatoida) associated with the scleractinian coral Pavona explanulata (Lamarck) from off Taiwan - Yu-Rong Cheng; Ju-shey Ho; Chang-Feng Dai (Systematic Parasitology, 2011)

Dietary patterns and breast cancer risk among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Jian-Hua Fu; Shou-Zhen Cheng; Yu-Ming Chen; Fang-Yu Lin (Cancer Causes & Control, 2011)

Two genetic divergence centers revealed by chloroplastic DNA variation in populations of Cinnamomum kanehirae Hay - Dai-Chang Kuo; Chia-Chia Lin; Kuo-Chieh Ho; Yu-Pin Cheng; Shih-Ying Hwang; Tsan-Piao Lin (Conservation Genetics, 2010)

Meat and egg consumption and risk of breast cancer among Chinese women - Cai-Xia Zhang; Suzanne C. Ho; Yu-Ming Chen; Fang-Yu Lin; Jian-Hua Fu; Shou-Zhen Cheng (Cancer Causes & Control, 2009)

Orstomella yaliuensis n. sp., a xarifiid copepod (Crustacea) parasitic in the polyps of hump coral Porites lutea Milne Edwards & Haime off Taiwan - Yu-Rong Cheng; Ju-shey Ho; Chang-Feng Dai (Systematic Parasitology, 2009)

Simultaneously monitoring the particle size distribution, morphology and suspended solids concentration in wastewater applying digital image analysis (DIA) - Ruey-Fang Yu; Ho-Wen Chen; Wen-Po Cheng; Mei-Ling Chu (Environmental Monitoring and Assessment, 2009)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

Evidence of hyperpycnal flows at the head of the meandering Kaoping Canyon off SW Taiwan - Cheng-Shing Chiang; Ho-Shing Yu (Geo-Marine Letters, 2008)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Measurements of Wastewater True Color by 4/6 Wavelength Methods and Artificial Neural Network - Ruey-Fang Yu; Ho-Wen Chen; Wen-Po Cheng; Mei-Ling Chu (Environmental Monitoring and Assessment, 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Reduced vascular β-adrenergic receptors and catecholamine response in rats with lead induced hypertension - Huoy-Rou Chang; Shun-Sheng Chen; Der-An Tsao; Juei-Tang Cheng; Chi-Kung Ho; Hsin-Su Yu (Archives of Toxicology, 1997)